An electrochemical immunobiosensor for dengue virus NS1 protein detection / Nadiya Taha Darwish - Nadiya Taha, Darwish (2016)

(untitled)
The dengue virus (DENV) is one of the most common viral diseases in South East Asia with 50-100 million cases being reported every year. Rapid and accurate diagnosis of dengue virus is important to avoid critical stage of the infection. A label-free electrochemical immunosensor was developed for direct detection of the dengue virus unstructured protein (NS1). The biosensing interface consists of antifouling moieties (zwitterionic molecules) and linker molecules where the linker molecule is used to immobilize the biorecognition molecules (monoclonal anti-NS1 IgG antibody). The combination of monoclonal antibodies and antifouling molecules is an innovative design that improves the ability of biosensor in detecting the target analyte in a complicated sample. The ratios of antifouling molecules 4-sulfophenyl (SP) and 4-trimethylammoniophenyl (TMAP) to linker molecules 1,4-phenylenediamine (PPD) or 4-aminobenzoic acid (PABA) that provided the greatest resistance to non-specific protein adsorptions of bovine serum albumin labelled with fluorescein isothiocyanate (BSA-FITC) and cytochrome c labelled with rhodamine B isothiocyanate (Cyt c- RBITC) were determined by confocal laser scanning microscopy (CLSM). As a standard control, 2-[2-(2-methoxyethoxy) ethoxy] acetic acid (OEG) was used due to its known antifouling properties. The combination of (SP:TMAP:PPD) with a ratio of 0.5:1.5:0.37 showed the best antifouling capability and the deposition of these molecules was confirmed by using X-ray photoelectron spectroscopy (XPS) and field emission scanning electron microscopy (FESEM). The immunosensor was prepared by modification of indium tin oxide (ITO) electrodes with SP: TMAP: PPD. Then, the gold nanoparticles (AuNPs) (20 nm) were attached. Thereafter, 1, 4-phenylenediamine (3 mM) was used to derivatize the AuNPs to help in attachment of the monoclonal anti-NS1 antibody. Differential Pulse Voltammetry (DPV) and Electrochemical Impedance Spectroscopy (EIS) were used to study the stepwise fabrication of the immunosensor and to obtain the calibration curve for the NS1 antigen. The NS1 detection was iv performed in Fe (CN)63-/Fe(CN)64-. The coefficient of determination (R2) and correlation coefficient (R) for the calibration curve obtained through DPV method were 0.85 and -0.74, respectively. With the EIS technique, the R2 obtained was 0.94 and the R obtained was 0.95. A good detection limit of 5 ng mL-1 was reached. The immunosensor showed good stability for 21 days with a relative standard deviation (RSD) of 0.1% and good reproducibility with RSD of 0.02%. The selectivity study showed that the immunosensor was specific to the NS1 antigen and also the change in charge transfer (Rct), before and after incubation of the biosensor in human serum albumin (HSA) and human IgG antibody solutions was only 1.9% and 10.2% respectively, as compared to the change in charge transfer when the immunosensor was incubated in 50 ng mL-1 NS1. The immunosensor had low cross reactivity with human sera infected with malaria parasites and that the change in Rct was only 5.2% as compared to the change in charge transfer when the immunosensor was incubated in 1 μg mL−1 NS1 solution. Therefore, this immunosensor is believed to have an excellent potential in the clinical application for diagnosis of the deadly DENV during the early phase of illness.